An appraisal of bilingual language policy implementation in South African higher education. Issue 2 (3rd May 2020) - Mthombeni, Zama M; Ogunnubi, Olusola
Abstract : The demand for promoting bilingual and multilingual language policies in African universities can be regarded as a decolonial force for driving pedagogical changes in teaching and learning. In South Africa, there have been polemic debates particularly on the need to include African languages as alternatives to English. This article intervenes in the increasing tensions about language policy implementation in tertiary institutions. The study utilises a qualitative methodology that blends secondary and primary data collected from semi-structured interviews and questionnaires from two campuses (Howard and Pietermaritzburg) of the University of KwaZulu-Natal (UKZN). Findings reveal that the UKZN academic staff and students have mixed feelings about the implementation of the bilingual language policy. The authors argue for the need to balance the use of African and non-African languages for teaching and learning. The study ends with a highlight of the challenges related to this Africanising project through language policies by emphasising key tenets for strengthening language policy implementation in South Africa.